Teacher perceptions of effects of professional development on teaching practice and student learning - Castañeda, Imelda R. (ProQuest Information and Learning Company, 2002)
This study sought to test whether multidimensional professional development programs are preferable to a traditional one, which, typically, consists of taking a graduate course. It compared teachers' perceptions about the effects of three programs for professional development on their teaching practice and student performance. Two of the programs, the Arts Integration Program and Job Shadowing Institute, were multidimensional models of professional development. The third was Technology Training, a traditional model of professional development. The purpose of the study was to contribute to the body of knowledge about teachers' perceptions of the effect of professional development on their teaching practice and their students' learning. The study included elementary, middle, and high school teachers as participants and survey respondents. It spanned three years. Descriptive data were collected to provide an accurate description of the three programs. Participant observations of professional development sessions, informal and formal interviews of teachers, administrators, and facilitators were among the data collection tools used during the first two years of the study to provide a detailed description of the actual programs. The main focus of the study was a survey of participants' perceptions of the effect of professional development on their teaching and their students' learning. Survey results indicated that teachers perceived that professional development could be most effective for improving their teaching practice and student learning when the professional development programs are intentional, on going, and systemic. The non-traditional, multidimensional professional development was found to be more effective than the traditional model. However, the results of the study also indicated that even a traditional model of professional development was perceived as having an impact on students' learning when applications were made to curricular content and when there was support for further training. Based on these findings, a model or 'scaffold' towards effective professional development was conceptualized using constructs and characteristics that might influence teaching practice and student learning. Results are discussed in the light of the limitations of the study, implications for education, and suggestions for future research.--Abstract.